2013
DOI: 10.11606/issn.2176-7262.v46i1p17-23
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de um protocolo de treinamento concorrente sobre fatores de risco para o acúmulo de gordura hepática de adolescentes obesos

Abstract: Modelo de estudo: Estudo prospectivo. Objetivo: Avaliar o efeito de um protocolo de treinamento concorrente com duração de 16 semanas sobre fatores de risco para o acúmulo de gordura hepática de jovens obesos. Metodologia: A amostra foi formada por 38 indivíduos obesos de ambos os sexos e com idade entre 12 e 15 anos. A obesidade foi atestada pelo percentual de gordura corporal, o qual foi estimado pela absortometria radiológica de dupla energia (DEXA). Adicionalmente, a quantidade de gordura localizada no tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
(20 reference statements)
1
6
2
Order By: Relevance
“…On the other hand, Porto et al 22 consider the resistance training program as an efficient tool in reducing body fat resulting from the negative energy balance, resulting from the energy consumed during and after strength training sessions, and increasing oxygen consumption and energy expenditure at rest, possibly due to an increase in muscle mass 23 . The results of the present study have shown that, in the group of adolescents, there was a reduction in IF in both with HS (-0.4) and without HS (-0.4), and group effect, showing that individuals with HS have higher IF values, which is already known according to literature, because this adiposity is a predictor of HS 13 . In addition, although not statistically significant, when analyzing the delta values, both groups, with and without HS, presented a reduction in body fat, but with a tendency for the group without HS to reduce more.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…On the other hand, Porto et al 22 consider the resistance training program as an efficient tool in reducing body fat resulting from the negative energy balance, resulting from the energy consumed during and after strength training sessions, and increasing oxygen consumption and energy expenditure at rest, possibly due to an increase in muscle mass 23 . The results of the present study have shown that, in the group of adolescents, there was a reduction in IF in both with HS (-0.4) and without HS (-0.4), and group effect, showing that individuals with HS have higher IF values, which is already known according to literature, because this adiposity is a predictor of HS 13 . In addition, although not statistically significant, when analyzing the delta values, both groups, with and without HS, presented a reduction in body fat, but with a tendency for the group without HS to reduce more.…”
Section: Discussionsupporting
confidence: 77%
“…Fat in the central region is associated with endocrine and metabolic disorders because it is close to the vital organs and has more vascularization and innervations 26 . Waist circumference is among the indicators of central obesity 27 , as well as high fat concentration in the trunk region, which are considered risk factors for the development of HS 13 . In this context, it is extremely essential to reduce these variables in the treatment of HS, as occurred in the present study, although without statistical significance, but being equally effective from the clinical point of view.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(massa gorda,6±5,(5)(6)(7)(8)9±6,2%; p=0,620), (massa corporal magra, TF= 9,0±5,3% x TC= 6,8±6,7%; p=0,431) e no GER (TF= 19,6±15,3% x TC= 10,7±24,5%; p=0,331 …”
mentioning
confidence: 99%
“…Several types of exercise programs have been used to improve body composition and increase REE in obese adolescents. Concurrent training, a model that combines aerobic and strength exercises in the same training session, seems to be a very interesting strategy, since it has shown to be beneficial in reducing total and relative fat and increasing muscle mass in obese adolescents 8,9 . Conversely, functional training, another widely commercially available training model nowadays 10,11 , consists of multiple-joint exercises that rely less on the use of equipment and stable bases, thus bringing the training program closer to daily life activities.…”
mentioning
confidence: 99%